Neuromodulatory effect of acrous calamus leaves extract on dopaminergic system in mice - VengadeshPrabu, K.; George, T.; VinothKumar, R.; Nancy, J.; Kalaivani, M.; Vijayapandi, P. (Sphinx Knowledge House, 2009)
Acorus calamus (Family: Araceae), available in India and many parts of world, found to have various Pharmacological activities such as analgesic, anti-convulsant, anti-spasmodic, anti-inflammatory, anti-bacterial, anti ulcer and cyto-protective. In present study, we have investigated effects of methanol (ACME) and acetone (ACAE) extract of Acorus calamus leaves against APM induced stereotypy and haloperidol induced catalepsy. APM induced stereotypy behavior, which reached peak at 15 min period. ACME (20 and 50 mg/Kg oral) administration significantly reversed stereotypy induced by APM. But ACAE at doses used (5, 20 and 50 mg/Kg oral) could not alter the stereotypy induced by APM. Whereas ACME (50 mg/Kg) and ACAE (20, 50 mg/Kg) administration significantly potentiated the haloperidol induced catalepsy in mice.